Biologic Medications for the Treatment of Psoriasis - Main Groups and Dosing System - Elsherbiny, Bedeer Sabry (Archives of Pharmacy and Pharmaceutical Sciences, 2023)
This review explores the evolving landscape of psoriasis treatment with a focus on the transformative impact of biologic drugs. Psoriasis, a prevalent and persistent skin condition characterized by red and scaly patches, historically relied on topical, phototherapeutic, and systemic treatments, each with limitations. The advent of biologics represents a significant advancement, offering targeted interventions by addressing specific immunologic mechanisms underlying the disease. Biologics are now considered the preferred systemic therapy for chronic moderate-to-severe plaque psoriasis, particularly when conventional treatments prove ineffective or present disadvantages. The review delineates the mechanisms of action for biologics targeting tumour necrosis factor-alpha (TNF-α), interleukin-17 (IL-17) and interleukin-23 (IL-23). Specific drugs under each category, including etanercept, infliximab, adalimumab, secukinumab, ustekinumab, and others, are detailed with recommended dosages. Biologics have demonstrated substantial effectiveness, with clinical trials and real-world studies showcasing significant improvements in disease severity and patient’s quality of life. Notably, these drugs exhibit rapid action, often yielding noticeable changes within weeks. While biologics have revolutionized psoriasis treatment, the review emphasizes the importance of judicious use due to potential side effects such as injection-site reactions and respiratory infections. Serious adverse events, including infections and autoimmune reactions, necessitate careful patient selection and monitoring for safety. In conclusion, biologics offer a precise and effective approach to psoriasis treatment, promising marked symptom improvement and enhanced quality of life. The review underscores the need for responsible utilization, considering patient-specific factors, and anticipates ongoing advancements in biologics for improved control over this chronic dermatitis.